THE LANGUAGE OF BEAUTY IN POETRY - Jabborova Dilafruz Sharofovna (International Journal of Literature and Language Studies, 2026)
This article explores the concept of beauty as expressed through the language of poetry, focusing on stylistic and semantic dimensions. Poetry is a unique form of literary expression in which language is manipulated through figurative devices, phonetic structures, and syntactic patterns to evoke aesthetic responses. The study aims to analyze how linguistic elements such as metaphor, imagery, symbolism, and sound patterns contribute to the construction of beauty in poetic texts. Using a qualitative stylistic analysis approach, the paper examines selected poetic examples and theoretical perspectives from linguistics and literary criticism. The findings suggest that beauty in poetry emerges not only from thematic content but also from the intricate interaction between language form and meaning. The study highlights the importance of stylistics as a bridge between linguistics and literature, offering a scientific framework for understanding aesthetic experience in poetic discourse.